Poverty dynamics: childhood experience on a low income - Taylor, SJ (2009)
The UK government has pledged to end child poverty by 2020. It is not known how far the measure of child poverty used by the government corresponds to differences in children’s experiences. Qualitative research on poverty has not generally been informed by the insights of dynamic research, which investigates duration, timing and transitions, among other temporal topics. Qualitative and quantitative methods have not generally been combined in social policy research on poverty, which limits the explanatory power of both. The thesis presents an analysis of the correspondence or lack of correspondence between qualitative and quantitative research on child poverty as a temporal experience. Semi-structured life history interviews were conducted with 15-21 year olds in Britain with experience of child poverty in the period 1997-2001. These were analysed alongside secondary analysis of the British Household Panel Survey (1991-2005). The qualitative respondents lived in households which took part in the survey, so there is a direct link between the two methods. The assumptions, methods and findings of dynamic poverty research are in general found to be a simplified and decontexualised version, rather than a misrepresentation of, the qualitative findings. Time formed an important part of the experience of poverty for children. It was not possible to fully match together exits from poverty with perceived improvements in circumstances, and entries into poverty with perceived deteriorations in circumstances, though this was partly due to limited recall and lack of contemporaneous knowledge. Nor were these changes clearly placed in time by respondents, in terms of duration and timing. Although most respondents did not explicitly engage with the idea of poverty as a personal experience, poverty-like accounts of disadvantage and difference were found in the accounts of all respondents. Thus, there is evidence for and against the way child poverty is currently measured.